Pendampingan Pembelajaran Public Speaking bagi Finalis Duta Seni Budaya Indonesia - Maharani, Desak Putu Putri (El-Mujtama: Jurnal Pengabdian Masyarakat, 2025)
The aim of this service is to provide assistance in public speaking learning for finalists of Indonesian Arts and Culture Ambassadors in order to improve their communication and presentation skills. As representatives of Indonesian culture, the finalists are expected to be able to convey cultural messages confidently and effectively on various occasions. This mentoring activity is carried out through a series of training which includes basic public speaking techniques, mastery of material, and development of public speaking skills. The methods used are interactive training, simulation and continuous evaluation. The results of this activity showed a significant increase in the public speaking skills of the finalists, both in terms of mastery of the material, speaking techniques, and their appearance in front of the audience. It is hoped that this assistance can make a positive contribution in improving the quality and credibility of the finalists for the Indonesian Arts and Culture Ambassadors in promoting the richness of Indonesian arts and culture at the national and international levels.